2017
DOI: 10.4103/aian.aian_369_16
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in children with status epilepticus during resuscitation in pediatric emergency department: A retrospective observational study

Abstract: Objectives:To study the clinical profile and predictors of outcome in children with status epilepticus (SE) during resuscitation in pediatric emergency department.Materials and Methods:This retrospective study was carried out in a tertiary care teaching hospital. Admission and resuscitation data of children, aged between 1 month and 12 years, treated for SE, between September 2013 and August 2014, were extracted using a standard data collection form. Our SE management protocol had employed a modified pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…As found in our study, evidence from literature shows that children with refractory status had more unfavourable outcome and mortality than those with abortive status [20,21] . We also found that unfavourable outcome was more commonly associated with those children who remained pain responsive or unresponsive 6 hrs after seizure control.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As found in our study, evidence from literature shows that children with refractory status had more unfavourable outcome and mortality than those with abortive status [20,21] . We also found that unfavourable outcome was more commonly associated with those children who remained pain responsive or unresponsive 6 hrs after seizure control.…”
Section: Discussionsupporting
confidence: 82%
“…This delay was in majority of cases the time taken in travelling the distance from the patient's homes to the nearest health care facility and then to our hospital. According to various literature, timely administration of AED from referring centre and thus avoiding delay in initiation of treatment significantly improved outcome [20,21] . Suboptimally organized pre-hospital services greatly affect the evaluation, management and transport of the acutely ill child to an appropriate facility [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…However, this is comparable to other studies on childhood status epilepticus. In a recent retrospective study on 610 children with status epilepticus, the authors reported mortality in 4.6% of the cases [16]. Children with status epilepticus overall have better outcomes than adults, likely because of the presence of relatively benign causes such as febrile status epilepticus and underlying epilepsy compared to adults in whom acute symptomatic causes such as stroke and central nervous systems are common.…”
Section: Discussionmentioning
confidence: 99%
“…Step 2 of PREM advocates a primary survey that employs a 60-second modified Rapid Cardio-Pulmonary Cerebral Assessment (online supplemental appendix 2: mRCPCA). 8 The modifications include evaluation for gallop; quality of heart sounds; liver span; comprehensive non-invasive blood pressure assessment (ie, systolic and diastolic pressures, pulse pressure and mean arterial pressure (MAP)), and eye signs of NCSE (online supplemental appendix 3: PREM chart)). These clinical findings were incorporated around the PAT and renamed as the PREM triangle (online supplemental appendix 4: PREM triangle).…”
Section: Problem Solving In Clinical Practicementioning
confidence: 99%
“…For example, in status epilepticus, the median time of seizure duration prior to hospital arrival was 45 min with virtually no deaths in Australia and New Zealand, 7 whereas in India the median time of seizure duration prior to hospital arrival was 172 min and the mortality rate was 4.6%. 8 The limited number of healthcare facilities in lowresource settings also results in long queues of patients waiting to be seen. It is therefore critical to have a way of rapidly recognising children who require urgent resuscitation.…”
Section: Introductionmentioning
confidence: 99%